High resolution (3+1) REMPI and dissociation of acetone via 3p ← n Rydberg transitions - Mejía-Ospino, E.; Álvarez, I.; Cisneros, C. (Revista Mexicana de Física, 2006)
Measurements of multiphoton ionization and dissociation of acetone are reported in the wavelength range 490.0-510.0 nm at 1 nm intervals. To our knowledge there are no available results of (3+1) REMPI on acetone in this region. The experiments were performed using an Nd:YAG-OPO (optical parametric oscillator) laser system coupled to a time-of-flight mass spectrometer. The experimental results show two dissociation channels of the acetone ion, leading to the products (CH_3CO^ + ) and (CH_3^ + ), the channel CH_3COCH_3^ + → CH_3CO^ + + CH_3^ being the most favored. The acetone and acetyl ions are observed in the entire wavelength range investigated. Finally, the three-photon resonance multiphoton spectrum of the acetone 3p ← n Rydberg transition is also reported.